Osteopontin as a diagnostic and NTZ-response biomarker of multiple sclerosis: a systematic review and meta-analysis - González-Jiménez, Adela; Urcelay, Elena; Espino-Paisán, Laura (Frontiers in Immunology, 2025)
IntroductionMultiple sclerosis (MS) is a neuroinflammatory complex disease of the central nervous system (CNS). Diagnosing MS remains challenging due to its nonspecific signs, highlighting the need for reliable biomarkers. One potential biomarker is osteopontin (OPN), found in cerebrospinal fluid (CSF) and peripheral blood. This article presents a systematic review and meta-analysis of the association between OPN levels in CSF and blood and the presence of MS.MethodsWe searched PubMed, Embase, and Cochrane databases for articles measuring OPN concentrations in peripheral blood and CSF samples from MS patients, published before July 12, 2024. A total of 605 articles were identified, and 29 were included in the analysis. Risk of bias was assessed with the NOS scale. The study protocol was officially registered in the PROSPERO website (registration number: CRD42023473406). We extracted standardized mean differences, 95% confidence intervals, and two-sided p values from each study and conducted a meta-analysis using a random-effects model. The heterogeneity among studies was evaluated by I-squared (I2), with values greater than 40% indicating high heterogeneity. Results and discussionThe present analysis revealed that individuals who suffered a first episode suggestive of MS, Clinically Isolated Syndrome (CIS), exhibited higher OPN levels in CSF than controls and patients with other neurological disorders (OND), emerging as an additional diagnosis tool. Furthermore, the observed decrease of OPN levels after Natalizumab (NTZ) treatment evidenced its potential as a biomarker of its efficacy. Higher OPN levels were found in CSF of individuals with MS compared to healthy controls (HC) and subjects with no other neurological diseases (NOND), result corroborated in relapsing remitting (RRMS) and secondary progressive (SPMS) patients. Similar OPN levels were observed when comparing MS patients to OND patients, suggesting that elevated OPN levels may be a common feature across various neurological conditions. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023473406.